Alleviating Ulcer Burdens Examining the Potential of Albizia Odoratissima Bark Extract as a Therapeutic Agent in Mice - Sultana, M. Tarannum; Basha, Shakir; Teja, Y. Sai Charan; S, Karthick. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Ulcerative stomach disease continues to be a prevalent gastrointestinal illness associated with high worldwide morbidity and medical costs. While nonsteroidal anti-inflammatory drugs (NSAIDs) and Helicobacter pylori infection are well-known risk factors for the development of peptic ulcers, recent evidence suggests a complex interaction between host factors and the gut microbiota in ulcer etiology. This study provides a comprehensive review of recent research investigating the relationship between the genesis and progression of peptic ulcers and dysbiosis of the gut microbiota. The study highlights several natural compounds, such as flavonoids, polyphenols, alkaloids, and polysaccharides, that have demonstrated anti-ulcer activity in experimental models and clinical trials. Mechanistic understanding clarifies the many pathways, including antibacterial, anti-inflammatory, and antioxidant ones, through which these drugs perform their medicinal effects. It is interesting to note that many natural compounds focus on many pathogenic procedures that aid in the development and spread of ulcers, resulting in multifactorial effects. Albizia odoratissima is a member of the Fabaceae family and has been used traditionally in many folk medicines due to its medicinal characteristics. This study used experimental models of stomach ulceration to investigate potential anti-ulcer properties of methanolic bark extract from Albizia odoratissima (MAO). The anti-ulcer qualities of MAO were evaluated in rats using models of stomach ulceration brought on by HCL. Many parameters were assessed when different doses of MAO were administered orally, including the ulcer index, mucosal injury to the stomach, mucin content, and antioxidant enzyme levels. Additionally, a histological analysis was carried out to evaluate the possible protective qualities of MAO against harm to the stomach mucosa.